PENGARUH PEMEKARAN KECAMATAN TERHADAP PEMBERIAN PELAYANAN DI KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI (STUDI KASUS SEKSI PEMERINTAHAN) - SELVIA, OKTI; ", SUJIANTO (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Effect of splitting expansion district Of Service. This study aims to determine how the effect of expansion on provision of service in District Sentajo Raya Regency Kuantan Singingi especially in the areas of governance section. This study menggunankan quantitative methods. The results showed the significant influence of the sub-district division to provision of services, with a correlation coefficient of 0.854 obtained are included in the category of very strong with an error level of 5%. Thus it can be seen that the variable division of districts accounted for 72.93% of the provision of services in the District Sentajo Raya Regency Kuantan Singingi.Keywords : Expansion area, service, organisation